The role of a conserved isoleucine in the structure, stability and function of human class alpha glutathione transferase A1-1 - Gordon, Graeme Patrick (My University, 2010)
Proteins have evolved to balance the structural requirements for stability with the need for specialised conformations imparting catalytic activity and ligand-binding capabilities. The glutathione transferases (GSTs) are a multi-gene family of ubiquitous proteins that are predominantly involved in the detoxification of reactive endo- and xenobiotic compounds through conjugation to the tripeptide glutathione. The family of cytosolic GSTs contain a canonical structure composed of a thioredoxin-like fold in domain 1 and an all-α-helical domain 2. Domain 1 of the cytosolic GSTs contains a highly conserved isoleucine residue in α-helix 3, located below the active site at position 71 in human class Alpha glutathione transferase A1-1 (hGST A1-1), that is involved in maintaining the packing within the hydrophobic core of domain 1. The objective of this study was to provide insight into the role of the topologically conserved Ile-71 residue in the structure, stability, and the catalytic and non-substrate ligandin function of hGST A1-1. This was achieved by introducing a cavitycreating mutation into hGST A1-1 by replacing Ile-71 with Val and comparing the structural and functional properties of the mutant with those of the wild-type protein. The structural properties of the mutant were the same as those of the wild-type protein as shown by far- and near-UV circular dichroism and tryptophan fluorescence studies. The stability of the mutant, however, was lower than that of he wild-type protein as revealed by a thermal-induced unfolding study which indicated that the temperature transition midpoint (Tm) value for the mutant (Tm = 54.71 ± 0.06 °C) was lower than that for the wild-type protein (Tm = 56.45 ± 0.02 °C). This finding is in agreement with that expected due to the loss of van der Waals contacts in the mutant protein. The catalytic properties of the mutant were found to be similar to those of the wild-type protein as indicated by a specific activity assay and a transition-state stabilisation study. Similarly, the non-substrate ligandin properties of the mutant were comparable to those of the wild-type protein as confirmed by 8-anilino-1-naphthalene sulfonate (ANS)-binding studies using active site ligands. This non-substrate ligand, ANS, is known to bind the H-site of the enzyme’s active site. This study reveals that although the Ile- 71 residue does not play a significant role in the structure and function of the protein, it makes a significant contribution to the stability of the protein by forming van der Waals contacts within the hydrophobic core of domain 1.